(untitled) (LEARNing Landscapes, 2022)
This commentary has been revised from a guest talk, with the same title, that the author delivered at the opening session of the Children and Youth Performance Conference III, presented by Young People’s Theatre and York University, online on June 25, 2021. The attendees were theatre practitioners, performers, community organizers, educators, and researchers working in the area of children and youth performance. This commentary attempts to demonstrate in practice “what we lose” when we only stage whiteness by focusing on the insights gained from centering the intellectual and artistic contributions of Black educators and Black theatre practitioners.